Human neutrophils produce extracellular traps against Paracoccidioides brasiliensis (2015)
ABSTRACT : Neutrophils play an important role as effector cells and contribute to the resistance of the host against microbial pathogens. Neutrophils are able to produce extracellular traps (NETs) in response to medically important fungi, including Aspergillus spp., Candida albicans and Cryptococcus gattii. However, NET production in response to Paracoccidioides brasiliensis has yet to be studied. We have demonstrated that human neutrophils produce NETs against both conidia and yeasts of P. brasiliensis. Although the NADPH oxidase inhibitor diphenyleneiodonium chloride (DPI) did not alter NET production against conidia, it partially suppressed NET formation against P. brasiliensis yeasts. Cytochalasin D or IFN-c did not affect the production of NETs against the fungus. Additionally, a mutant strain of P. brasiliensis with reduced expression of an alternative oxidase induced significantly higher levels of NETs in comparison with the WT strain. Finally, c.f.u. quantification of P. brasiliensis showed no significant differences when neutrophils were treated with DPI, DNase I or cytochalasin D as compared with untreated cells. These data establish that NET formation by human neutrophils appears to be either dependent or independent of reactive oxygen species production, correlating with the fungal morphotype used for stimulation. However, this mechanism was ineffective in killing the fungus.